Two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane as well as preparation method and application thereof
By combining two-dimensional porous F-Ce nanosheets with PVA, an efficient hybrid matrix membrane was prepared, which solved the problem that existing PVA membranes cannot have both permeability and selectivity in caprolactam dehydration, and achieved high permeability flux, High selectivity and high stability effects.
Patent Information
- Application Number
- CN202411287357.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing PVA films have problems that they cannot have both permeability and selectivity during the dehydration of permeable caprolactam, and the interface compatibility between traditional inorganic fillers and polymer matrix is poor, resulting in deterioration of membrane selectivity.
By combining two-dimensional porous F-Ce nanosheets with polyvinyl alcohol (PVA), the high surface area and nano thickness of the two-dimensional porous F-Ce nanosheets are used to prepare a hybrid matrix membrane with two-dimensional porous F-Ce nanosheets and The strong interaction of PVA improves the permeability and selectivity of the membrane, and improves the stability of the membrane through specific preparation methods.
Achieved high permeability flux, high selectivity and high stability permeability vaporized membrane materials, solving the problems of poor permeability flux and separation factors and poor membrane stability in the process of caprolactam dehydration of traditional membranes, and it is simple to operate and easy to scale. Chemical production.
Smart Images

Figure CN119113827A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane and a preparation method and application thereof, belonging to the technical field of pervaporation membrane separation. Background Art
[0002] ε-Caprolactam (CPL) is an important organic chemical raw material, mainly used to produce high-quality polyamide fibers and nylon, and is crucial to the development of the national economy. The main industrial production of CPL includes cyclohexanone-hydroxylamine method, toluene oxidation method, cyclohexane photonitrosation method, etc. The crude product contains 65-70wt% CPL, and the rest is mainly ammonium salt and water. CPL is a heat-sensitive substance with a higher boiling point than water. The presence of water will inhibit the growth of the polymerization reaction chain of CPL, seriously affecting the production quality of chemical fibers. Therefore, efficient dehydration of CPL is a crucial step. Traditional CPL dehydration technologies, such as triple-effect evaporation, crystallization and melt crystallization, have the disadvantages of complex process and low mass transfer efficiency. In comparison, pervaporation membrane separation technology has the advantages of high separation efficiency, low energy consumption, simple operation, environmentally friendly and clean, and the process is not limited by vapor-liquid equilibrium. It is widely used in the field of organic dehydration, and high-performance separation membrane materials are the key components of pervaporation technology.
[0003] Polyvinyl alcohol (PVA) has the characteristics of low price, strong film-forming property and excellent stability. It is one of the most industrially applied membrane materials in the field of pervaporation organic dehydration. However, the existing PVA membrane generally has the "trade-off" problem that permeability and selectivity cannot be achieved at the same time, which limits its industrial application. In order to solve this problem, researchers introduced zeolite, molecular sieve and other inorganic fillers into the PVA matrix to prepare mixed matrix membranes (MMMs) to improve the permeation flux and separation factor of the membrane. Lin et al. (Desalination, 2012, 285, 39-45) introduced nano-silica into the PVA membrane to prepare a mixed matrix membrane with enhanced caprolactam dehydration performance. However, these traditional inorganic fillers such as zeolite and molecular sieve have poor interfacial compatibility with the polymer matrix, are prone to agglomeration, and are prone to form non-selective defects during the membrane preparation process, which deteriorates the membrane selectivity. Therefore, it is urgent to develop a new type of mixed matrix membrane filled with inorganic porous materials to further improve the membrane separation performance and stability. Summary of the invention
[0004] The purpose of the present invention is to provide an efficient and stable two-dimensional porous nanosheet / PVA mixed matrix membrane and a preparation method thereof, which are used for pervaporation caprolactam dehydration and improve the permeability, selectivity and stability of the membrane material in pervaporation caprolactam dehydration.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] The present invention provides a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane. The two-dimensional porous F-Ce nanosheet is introduced into a polyvinyl alcohol (PVA) solution to obtain a casting solution, and then the casting solution is coated on a porous supporting substrate to prepare a thin and defect-free two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane for pervaporation dehydration of caprolactam.
[0007] The polyvinyl alcohol (PVA) is selected from one or more of PVA 105, PVA 117, PVA 124, PVA 1788, PVA 1792, PVA 1799, and PVA 2488;
[0008] The porous support substrate is made of any one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyacrylonitrile, polysulfone, polyethersulfone, and ceramics, and has a flat plate, tubular, or hollow fiber shape.
[0009] The present invention provides a method for preparing a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, and the specific preparation steps include:
[0010] 1) Dissolve cerium acetate in deionized water treated with high-purity nitrogen to obtain solution 1, the concentration of which is 1 to 5 g·L -1 ;
[0011] 2) Dissolve sodium fluoride in deionized water treated with high-purity nitrogen to obtain solution 2, the concentration of which is 0.5-3 g·L -1 ;
[0012] 3) adding the solution 2 dropwise into the solution 1, stirring at room temperature for 1 to 12 hours to obtain a suspension; wherein the volume ratio of the solution 1 to the solution 2 is 2:1 to 5:1;
[0013] 4) washing the suspension obtained in step 3) by centrifugation, freeze-drying, and obtaining the two-dimensional porous F-Ce nanosheets;
[0014] 5) PVA was dissolved in deionized water at 80-95°C to obtain solution 3, the concentration of which was 20-50 g·L -1 ;
[0015] 6) adding a crosslinking agent to the solution 3 and stirring for 10 to 60 minutes to obtain a solution 4;
[0016] The cross-linking agent is one or more of boric acid, glutaraldehyde, maleic acid, maleic acid, dimethylol urea, trimethylol melamine, sulfonated succinic acid, 4-sulfophthalic acid, and polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer; the mass ratio of the cross-linking agent to the PVA is 0.05:1 to 0.5:1;
[0017] 7) Take 0.1~2mol L -1 The catalyst is added dropwise to the solution 4, the pH is adjusted to 1-5, stirring is continued for 3-6 hours, heating is stopped and the temperature is cooled to room temperature to obtain a solution 5;
[0018] The catalyst is one of sulfuric acid and hydrochloric acid;
[0019] 8) Add 0.1-1 mol L -1 The alkaline aqueous solution was adjusted to pH 7-12 and stirred for 10 min-6 h to obtain solution 6;
[0020] The alkaline substance is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium amide, ammonia water, ethanolamine, diethanolamine, and triethylamine;
[0021] 9) introducing the two-dimensional porous F-Ce nanosheets obtained in step 4) into the solution 6, dispersing by ultrasonication, and standing to degas, thereby obtaining a casting solution 7;
[0022] The mass ratio of the two-dimensional porous F-Ce nanosheets to the PVA in the solution 6 is 0.02:1 to 0.1:1;
[0023] 10) The casting solution 7 is coated onto a porous supporting substrate with a thickness of 50 to 500 μm, and dried at 80 to 120° C. for 10 min to 6 h to obtain a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane.
[0024] The present invention also provides a two-dimensional porous F-Ce nanosheet prepared based on the above preparation method
[0025] / PVA mixed matrix film.
[0026] The present invention also provides an application of a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane in pervaporation caprolactam dehydration.
[0027] Beneficial Effects
[0028] Compared with the prior art, the advantages and positive effects of the present invention are:
[0029] 1. The two-dimensional F-Ce nanosheets have a strong interaction with the polymer PVA due to their large surface area, nanometer thickness and high aspect ratio. The two have good interfacial compatibility, which solves the problem of poor compatibility between inorganic fillers and polymer matrices in traditional mixed matrix membranes.
[0030] 2. The porous F-Ce two-dimensional nanosheets have efficient transfer channels for water molecules and excellent stability, and enhance the membrane's anti-swelling ability, solving the problems of poor permeation flux and separation factor and poor membrane stability in the process of caprolactam dehydration of traditional pervaporation mixed matrix membranes.
[0031] 3. The present invention introduces two-dimensional porous F-Ce nanosheets into polyvinyl alcohol for the first time to prepare a mixed matrix membrane for pervaporation caprolactam dehydration. The membrane preparation method is simple to operate, has mild preparation conditions, and is easy to scale up production, providing the much-needed pervaporation membrane material with high permeation flux, high selectivity and high stability for the field of caprolactam dehydration. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the two-dimensional porous F-Ce nanosheet obtained in step 4) of Example 3;
[0033] Figure 2 The AFM image of the two-dimensional porous F-Ce nanosheet obtained in step 4) of Example 3;
[0034] Figure 3 This is a low-magnification TEM image of the two-dimensional porous F-Ce nanosheet obtained in step 4) of Example 3;
[0035] Figure 4 This is a high-magnification TEM image of the two-dimensional porous F-Ce nanosheet obtained in step 4) of Example 3;
[0036] Figure 5 This is a high-magnification SEM image of the surface of the two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane obtained in Example 3;
[0037] Figure 6 This is a high-magnification SEM image of the cross section of the two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane obtained in Example 3;
[0038] Figure 7 The pervaporation caprolactam dehydration performance diagram of the F-Ce / PVA mixed matrix membrane obtained in Examples 1-4 and the membrane material prepared in Comparative Examples 1-2.
[0039] Figure 8 The swelling performance diagram of the F-Ce / PVA mixed matrix membranes obtained in Examples 1-4 and the membrane material prepared in Comparative Example 1 in water. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0041] Example 1
[0042] 1) dissolving 1.1 g of cerium acetate in 260 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 1;
[0043] 2) dissolving 0.12 g of sodium fluoride in 100 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 2;
[0044] 3) Add solution 2 dropwise into solution 1 under stirring, and react at room temperature for 3 h to obtain a suspension;
[0045] 4) washing the suspension obtained in step 3) by centrifugation, freeze-drying, and obtaining the two-dimensional porous F-Ce nanosheets;
[0046] 5) Dissolve 5 g of PVA 1799 in 100 mL of deionized water at 95° C. and stir for 3 h to obtain solution 3;
[0047] 6) adding 2.14 g of polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer to solution 3 and stirring for 30 min to obtain solution 4;
[0048] 7) Take 1 mol L -1 Aqueous sulfuric acid solution was added dropwise to solution 4, the pH was adjusted to 1, stirring was continued for 6 h, heating was stopped and the temperature was cooled to room temperature to obtain solution 5;
[0049] 8) Add 1 mol L -1 Sodium hydroxide aqueous solution, adjust pH to 9, continue stirring for 30 min to obtain solution 6;
[0050] 9) introducing 0.1 g of the two-dimensional porous F-Ce nanosheet obtained in step 4) into solution 6, performing ultrasonic dispersion for 30 min, and standing for degassing to obtain a casting solution 7;
[0051] 10) The casting solution 7 was coated onto a polyacrylonitrile porous flat substrate with a thickness of 150 μm, and dried at 100° C. for 30 min to obtain a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, labeled as F-Ce / PVA-2.
[0052] Example 2
[0053] 1) dissolving 1.1 g of cerium acetate in 260 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 1;
[0054] 2) dissolving 0.12 g of sodium fluoride in 100 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 2;
[0055] 3) Add solution 2 dropwise into solution 1 under stirring, and react at room temperature for 3 h to obtain a suspension;
[0056] 4) washing the suspension obtained in step 3) by centrifugation, freeze-drying, and obtaining the two-dimensional porous F-Ce nanosheets;
[0057] 5) Dissolve 5 g of PVA 1799 in 100 mL of deionized water at 95° C. and stir for 3 h to obtain solution 3;
[0058] 6) adding 2.14 g of polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer to solution 3 and stirring for 30 min to obtain solution 4;
[0059] 7) Take 1 mol L -1 Aqueous sulfuric acid solution was added dropwise to solution 4, the pH was adjusted to 1, stirring was continued for 6 h, heating was stopped and the temperature was cooled to room temperature to obtain solution 5;
[0060] 8) Add 1 mol L -1 Sodium hydroxide aqueous solution, adjust pH to 9, continue stirring for 30 min to obtain solution 6;
[0061] 9) introducing 0.2 g of the two-dimensional porous F-Ce nanosheet obtained in step 4) into solution 6, performing ultrasonic dispersion for 30 min, and standing for degassing to obtain a casting solution 7;
[0062] 10) The casting solution 7 was coated onto a polyacrylonitrile porous flat substrate with a thickness of 150 μm, and dried at 100° C. for 30 min to obtain a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, labeled as F-Ce / PVA-4.
[0063] Example 3
[0064] 1) dissolving 1.1 g of cerium acetate in 260 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 1;
[0065] 2) dissolving 0.12 g of sodium fluoride in 100 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 2;
[0066] 3) Add solution 2 dropwise into solution 1 under stirring, and react at room temperature for 3 h to obtain a suspension;
[0067] 4) The suspension obtained in step 3) is centrifuged, washed, and freeze-dried to obtain the two-dimensional porous F-Ce nanosheet; the SEM image of the two-dimensional porous F-Ce nanosheet is as follows: Figure 1 As shown in the AFM image Figure 2 As shown, low magnification TEM images are shown Figure 3 As shown, high magnification TEM images are shown Figure 4 As shown;
[0068] 5) Dissolve 5 g of PVA 1799 in 100 mL of deionized water at 95° C. and stir for 3 h to obtain solution 3;
[0069] 6) adding 2.14 g of polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer to solution 3 and stirring for 30 min to obtain solution 4;
[0070] 7) Take 1 mol L -1 Aqueous sulfuric acid solution was added dropwise to solution 4, the pH was adjusted to 1, stirring was continued for 6 h, heating was stopped and the temperature was cooled to room temperature to obtain solution 5;
[0071] 8) Add 1 mol L -1 Sodium hydroxide aqueous solution, adjust pH to 9, continue stirring for 30 min to obtain solution 6;
[0072] 9) introducing 0.3 g of the two-dimensional porous F-Ce nanosheet obtained in step 4) into solution 6, performing ultrasonic dispersion for 30 min, and standing for degassing to obtain a casting solution 7;
[0073] 10) The casting solution 7 was coated onto a polyacrylonitrile porous flat substrate with a thickness of 150 μm, and dried at 100° C. for 30 min to obtain a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, labeled as F-Ce / PVA-6; the high-magnification SEM image of the surface of F-Ce / PVA-6 is shown in FIG. Figure 5 As shown, the cross-sectional high-magnification SEM image of F-Ce / PVA-6 is shown in Figure 6 shown.
[0074] Example 4
[0075] 1) dissolving 1.1 g of cerium acetate in 260 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 1;
[0076] 2) dissolving 0.12 g of sodium fluoride in 100 mL of deionized water treated with high-purity nitrogen for 30 min to obtain solution 2;
[0077] 3) Add solution 2 dropwise into solution 1 under stirring, and react at room temperature for 3 h to obtain a suspension;
[0078] 4) washing the suspension obtained in step 3) by centrifugation, freeze-drying, and obtaining the two-dimensional porous F-Ce nanosheets;
[0079] 5) Dissolve 5 g of PVA 1799 in 100 mL of deionized water at 95° C. and stir for 3 h to obtain solution 3;
[0080] 6) adding 2.14 g of polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer to solution 3 and stirring for 30 min to obtain solution 4;
[0081] 7) Take 1 mol L -1 Aqueous sulfuric acid solution was added dropwise to solution 4, the pH was adjusted to 1, stirring was continued for 6 h, heating was stopped and the temperature was cooled to room temperature to obtain solution 5;
[0082] 8) Add 1 mol L -1 Sodium hydroxide aqueous solution, adjust pH to 9, continue stirring for 30 min to obtain solution 6;
[0083] 9) introducing 0.4 g of the two-dimensional porous F-Ce nanosheet obtained in step 4) into solution 6, performing ultrasonic dispersion for 30 min, and standing for degassing to obtain a casting solution 7;
[0084] 10) The casting solution 7 was coated onto a polyacrylonitrile porous flat substrate with a thickness of 150 μm, and dried at 100° C. for 30 min to obtain a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, labeled as F-Ce / PVA-8.
[0085] Comparative Example 1
[0086] 1) Dissolve 5 g of PVA 1799 in 100 mL of deionized water at 95° C. and stir for 3 h to obtain solution 1;
[0087] 2) adding 2.14 g of polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer to solution 1 and stirring for 30 min to obtain solution 2;
[0088] 3) Take 1 mol L -1 Aqueous sulfuric acid solution was added dropwise to solution 2, the pH was adjusted to 1, stirring was continued for 6 h, heating was stopped and the temperature was cooled to room temperature to obtain solution 3;
[0089] 4) Add 1 mol L to solution 3 -1 Sodium hydroxide aqueous solution, adjust pH to 9, continue stirring for 30 minutes, stand and degas, and obtain casting solution 4;
[0090] 5) The casting solution 4 was coated onto a polyacrylonitrile porous flat substrate with a thickness of 150 μm, and dried at 100° C. for 30 min to obtain a PVA composite membrane, which was labeled as PVA / PAN.
[0091] Comparative Example 2
[0092] 1) Dissolve 5 g of PVA 1799 in 100 mL of deionized water at 95° C. and stir for 3 h to obtain solution 1;
[0093] 2) adding 2.14 g of polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer to solution 3 and stirring for 30 min to obtain solution 2;
[0094] 3) Take 1 mol L -1 Aqueous sulfuric acid solution was added dropwise to solution 2, the pH was adjusted to 1, stirring was continued for 6 h, heating was stopped and the temperature was cooled to room temperature to obtain solution 3;
[0095] 4) Add 1 mol L to solution 3 -1 Sodium hydroxide aqueous solution, adjust pH to 9, continue stirring for 30 min to obtain solution 4;
[0096] 5) 0.3 g of nano-silicon dioxide particles (diameter 10-20 nm) were introduced into solution 4, and ultrasonically dispersed for 30 min. After standing and degassing, a casting solution 5 was obtained;
[0097] 6) The casting solution 5 was coated onto a polyacrylonitrile porous flat substrate with a thickness of 150 μm, and dried at 100° C. for 30 min to obtain a nano-silica particle / PVA mixed matrix membrane, which was labeled as Silica / PVA-6.
[0098] The membrane materials prepared in Examples 1-4 and Comparative Examples 1-2 were passed through a pervaporation device to test their caprolactam dehydration performance. The results are as follows: Figure 7 The specific test standards are as follows:
[0099] The effective area of the membrane used in the test is 12 cm 2 The raw material liquid is 70wt% caprolactam aqueous solution, and the raw material liquid circulation flow rate is 40L h -1 , the test system temperature was maintained at 40°C. A vacuum pump was used to maintain the permeate pressure below 300Pa, and the collector was immersed in liquid nitrogen to collect the permeate components. The raw liquid and permeate components were tested with a UV-6100 ultraviolet spectrophotometer (Shanghai Meipuda Instrument Co., Ltd.). Each membrane was measured at least three times and the average value was taken. The total permeate flux (J, gm) was calculated according to the following equation: -2 h -1 ) and separation factor (β):
[0100]
[0101] Where W (g) is the total mass of the permeate, A (m 2 ) is the effective area of the membrane, and t(h) is the test time. i and i Represent the mass concentration (wt%) of caprolactam in the raw liquid and the permeate, respectively.
[0102] To test the swelling degree of the membrane material, the membrane sample must first be dried in a 60°C oven for 24 hours, and then the dried membrane sample must be fully immersed in water for 72 hours. The swollen membrane sample is wiped dry with filter paper and the mass is recorded. By measuring the mass of the dry and swollen membranes, the swelling degree (DS) of the prepared membrane in water can be known, and the calculation method is as follows:
[0103]
[0104] Where Wd(g) is the mass of the dry film and Ww(g) is the mass of the film after swelling.
[0105] Depend on Figure 7 It can be seen that in Examples 1-4, two-dimensional porous F-Ce nanosheets were introduced into the PVA matrix to prepare high-performance mixed matrix membranes, whose permeation flux and separation factor were much higher than those of the membrane materials prepared in Comparative Examples 1-2. The permeation flux and separation factor of the mixed matrix membrane prepared in Example 3 were 1363 g m -2 h -1 and 1554, which are significantly higher than the 700 g m of the PVA / PAN film prepared in Comparative Example 1. -2 h -1 and 750, and significantly higher than the 820 g m of the Silica / PVA-6 film filled with conventional inorganic material silica prepared in Comparative Example 2. -2 h -1 and 906. Depend on Figure 8 It can be seen that as the filling amount of the two-dimensional porous F-Ce nanosheets increases, the swelling degree of the prepared F-Ce nanosheet / PVA mixed matrix membrane in water gradually decreases, and is lower than the swelling degree of the PVA membrane in water. The above results show that the PVA mixed matrix membrane filled with two-dimensional porous F-Ce nanosheets used in the present invention has excellent separation performance in the application of caprolactam dehydration, and the permeation flux, separation factor and anti-swelling are significantly improved, and the operation is simple and easy to prepare on a large scale.
[0106] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, characterized in that: Two-dimensional porous F-Ce nanosheets are introduced into a PVA solution to obtain a casting solution, which is then coated onto a porous supporting substrate to prepare a thin and defect-free two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane for pervaporation dehydration of caprolactam.
2. The two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane according to claim 1, characterized in that: The PVA is selected from one or more of PVA 105, PVA 117, PVA 124, PVA 1788, PVA 1792, PVA 1799, and PVA 2488.
3. The two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane according to claim 1, characterized in that: The porous support substrate is an organic porous material or an inorganic porous material, and its shape is a flat plate, a tube or a hollow fiber.
4. The two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane according to claim 1, characterized in that: The porous support substrate is made of any one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyacrylonitrile, polysulfone, polyethersulfone and ceramic.
5. The method for preparing the two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane according to any one of claims 1 to 4, characterized in that: The specific preparation steps include: 1) Dissolve cerium acetate in deionized water treated with high-purity nitrogen to obtain solution 1, the concentration of which is 1 to 5 g·L -1 ; 2) Dissolve sodium fluoride in deionized water treated with high-purity nitrogen to obtain solution 2, the concentration of which is 0.5-3 g·L -1 ; 3) adding the solution 2 dropwise into the solution 1, stirring at room temperature for 1 to 12 hours to obtain a suspension; wherein the volume ratio of the solution 1 to the solution 2 is 2:1 to 5:1; 4) washing the suspension obtained in step 3) by centrifugation, freeze-drying, and obtaining the two-dimensional porous F-Ce nanosheets; 5) PVA was dissolved in deionized water at 80-95°C to obtain solution 3, the concentration of which was 20-50 g·L -1 ; 6) adding a crosslinking agent to the solution 3 and stirring for 10 to 60 minutes to obtain a solution 4; The cross-linking agent is one or more of boric acid, glutaraldehyde, maleic acid, maleic acid, dimethylol urea, trimethylol melamine, sulfonated succinic acid, 4-sulfophthalic acid, and polyacrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer; the mass ratio of the cross-linking agent to the PVA is 0.05:1 to 0.5:1; 7) Take 0.1~2molL -1 The catalyst is added dropwise to the solution 4, the pH is adjusted to 1-5, stirring is continued for 3-6 hours, heating is stopped and the temperature is cooled to room temperature to obtain a solution 5; The catalyst is one of sulfuric acid and hydrochloric acid; 8) Add 0.1-1 molL -1 The alkaline aqueous solution was adjusted to pH 7-12 and stirred for 10 min-6 h to obtain solution 6; The alkaline substance is one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium amide, ammonia water, ethanolamine, diethanolamine, and triethylamine; 9) introducing the two-dimensional porous F-Ce nanosheets obtained in step 4) into the solution 6, performing ultrasonic dispersion, and standing for degassing to obtain a casting solution 7; The mass ratio of the two-dimensional porous F-Ce nanosheets to the PVA in the solution 6 is 0.02:1 to 0.1:1; 10) The casting solution 7 is coated onto a porous supporting substrate with a thickness of 50 to 500 μm, and dried at 80 to 120° C. for 10 min to 6 h to obtain a two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane.
6. A two-dimensional porous F-Ce nanosheet / PVA mixed matrix membrane, characterized in that: The mixed matrix membrane is prepared according to the preparation method according to claim 5.
7. Use of the mixed matrix membrane according to any one of claims 1 to 4 and 6 in pervaporation caprolactam dehydration.
Citation Information
Patent Citations
Preparation method of polyvinyl alcohol / graphite-phase carbon nitride pervaporation hybrid membrane
CN106268332A
Graphene oxide@polyvinyl alcohol mixed matrix pervaporation membrane and preparation method thereof
CN108479423A
Lanthanide fluoride two-dimensional nanosheet membrane and preparation method and application thereof
CN113351036A
Cerium fluoride porous nanosheet regulated mixed matrix membrane, preparation method and application thereof
CN113896220A
Ionic liquid modified cerium fluoride porous nanosheet regulated mixed matrix membrane, preparation method and application thereof
CN113967412A
